Seed priming using moringa leaf extract and application of Tithonia compost on shallot growth - Mantja, Katriani; Syam'un, Elkawakib; Faried, Muhammad (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2023)
Early establishment of shallot growth is important in order to ensure optimum yield. This study aimed to evaluate the effect of seed priming with moringa leaf extract (MLE) and the application of Tithonia compost on the growth of shallots. The research was conducted at the experimental farm belonging to the Faculty of Agriculture, Hasanuddin University, Makassar, from September to December 2022. The study was arranged in a factorial design with three replications. The first factor was priming, consisting of five levels: unprimed, hydropriming, 12.5% MLE, 25% MLE, and 37.5% MLE. The second factor was the level of Tithonia compost, consisting of four levels: 0, 5, 10, and 15 tons ha-1. The results revealed that shallots treated with a combination of priming 37.5% MLE followed by application of 15 tons ha-1 of Tithonia compost in the field had the highest chlorophyll index (25.97). Priming with 37.5% solely resulted in the highest average shallots height (38.23 cm), the number of plant leaves (10.55), leaf weight (15.67 g), and bulb weight (29.92 g). Application of Tithonia compost solely of 15 tons ha-1 produced shallot with the highest average plant height (37.72 cm), the number of plant leaves (9.74), leaf weight (13.68 g), and bulb weight (27.01 g). Seed priming using MLE and application of Tithonia compost are prospective to enhance shallots growth, however, it is important to further evaluate the effect of priming on germination traits and economic evaluation on using Tithonia compost for practical applications in the field. Keywords: botanical seed; organic matter; leaf extract